Differences in siRNA encapsulation between HsaHFt-RK ferritin and EcaLHFt - Charousová, Markéta; Mokrý, Michal; Pekařík, Vladimír (Mendel University in Brno, 2019)
Nanomedicine in cancer treatment has a great potential. With usage of proper nanocarrier we would be able to eliminate negative side effects and excessively high toxicity of chemotherapeutical drugs to normal cells. Ferritins in general are proteins which could do the trick. Their ability to change structure in low pH could be used for drug delivery. Ferritins are also ubiquitous so there is also very small chance of immune reaction in body. First and the most used and described ferritin is EcaLHFt (ferritin from horse spleen). Its ability to encapsulate various molecules is already known and used in research laboratories. Only molecules with negative charge are troublesome to encapsulate into EcaLHFt. For this reason, we created recombinant human ferritin – HsaHFt-RK, which is designed to encapsulate predominantly negatively charged molecules. We were able to confirm this hypothesis by comparing the encapsulation efficiency of FAM-siRNA inside EcaLHFt and HsaHFt-RK.

Nanomedicine in cancer treatment has a great potential. With usage of proper nanocarrier we would be able to eliminate negative side effects and excessively high toxicity of chemotherapeutical drugs to normal cells. Ferritins in general are proteins which could do the trick. Their ability to change structure in low pH could be used for drug delivery. Ferritins are also ubiquitous so there is also very small chance of immune reaction in body. First and the most used and described ferritin is EcaLHFt (ferritin from horse spleen). Its ability to encapsulate various molecules is already known and used in research laboratories. Only molecules with negative charge are troublesome to encapsulate into EcaLHFt. For this reason, we created recombinant human ferritin – HsaHFt-RK, which is designed to encapsulate predominantly negatively charged molecules. We were able to confirm this hypothesis by comparing the encapsulation efficiency of FAM-siRNA inside EcaLHFt and HsaHFt-RK.
Differences in siRNA encapsulation between HsaHFt-RK ferritin and EcaLHFt
Keywords: nanomedicine; ferritin; gene therapy; siRNA; recombinant protein; nanomedicine; ferritin; gene therapy; siRNA; recombinant protein